Effects of empagliflozin on progression of chronic kidney disease: a prespecified secondary analysis from the empa-kidney trial - Staplin, N; Haynes, R; Herrington, W; Judge, P; Emberson, J; Preiss, D; Mayne, K; Sammons, E; Zhu, D; Hill, M; Stevens, W; Wallendszus, K; et al. (Elsevier, 2023)
Background Sodium–glucose co-transporter-2 (SGLT2) inhibitors reduce progression of chronic kidney disease and the risk of cardiovascular morbidity and mortality in a wide range of patients. However, their effects on kidney disease progression in some patients with chronic kidney disease are unclear because few clinical kidney outcomes occurred among such patients in the completed trials. In particular, some guidelines stratify their level of recommendation about who should be treated with SGLT2 inhibitors based on diabetes status and albuminuria. We aimed to assess the effects of empagliflozin on progression of chronic kidney disease both overall and among specific types of participants in the EMPA-KIDNEY trial.